The Kalayaan naval oceanographic atlas. (Makati City Naval Intelligence and Security Force, 2000)
Scientific results of the German Atlantic Expedition of the Research Vessel Meteor, 1925-1927; vol. 5 with atlas
Keywords: Reefs--Rota--Atlases.; Philippines--Maps.; Density--Atlantic ocean; Oceanography--Kalayaan Island--Charts, diagrams, etc; Oceanography--Spratly Island--Charts, diagrams, etc